Short report: Evidence of non-masticatory dental use in Bronze Age individuals exhumed from the Necropolis of Casas Velhas (Portugal) - Silva, Ana Maria (2018)
The Southwest Iberian Middle Bronze Age culture, although widespread in southern Portugal and nearby areas of southwest Spain in the Middle Bronze Age, is characterised by the scarcity of preserved human remains. Recent reanalysis of the human remains unearthed from the grave cists of the necropolis of Casas Velhas (Melides, Portugal), with a minimal number of 21 individuals (19 adults and 2 non-adults), included the analysis of the dental remains to assess information about non-masticatory behaviour and oral pathology of these individuals. Dental data scored included dental wear, oral lesions (chipping and grooves), and atypical dental wear patterns. The mean dental wear is low (2.93; n=90), although 16 teeth exhibit severe dental wear (> grade 4). Only one tooth displays a cariogenic lesion (1/82). Atypical dental wear patterns, chipping and the presence of grooves were recorded in six individuals (6/11 = 54.5%). The predominant anterior pattern of unusual dental wear and oral lesions were interpreted as highly suggestive of the use of anterior teeth in extra-masticatory activities. The chips observed in posterior teeth were interpreted as mainly resulting from masticatory activities, as the ingestion of hard foods. The obtained results were discussed in terms of a more vegetarian diet proposed for these individuals, as well as, the use of vegetable products, as the treatment of vegetable fibres in daily activities.